Fabrication of Defined Polydopamine Nanostructures by DNA Origami‐Templated Polymerization. (15th January 2018) - Tokura, Yu; Harvey, Sean; Chen, Chaojian; Wu, Yuzhou; Ng, David Y. W.; Weil, Tanja
Abstract: A versatile, bottom‐up approach allows the controlled fabrication of polydopamine (PD) nanostructures on DNA origami. PD is a biosynthetic polymer that has been investigated as an adhesive and promising surface coating material. However, the control of dopamine polymerization is challenged by the multistage‐mediated reaction mechanism and diverse chemical structures in PD. DNA origami decorated with multiple horseradish peroxidase‐mimicking DNAzyme motifs was used to control the shape and size of PD formation with nanometer resolution. These fabricated PD nanostructures can serve as "supramolecular glue" for controlling DNA origami conformations. Facile liberation of the PD nanostructures from the DNA origami templates has been achieved in acidic medium. This presented DNA origami‐controlled polymerization of a highly crosslinked polymer provides a unique access towards anisotropic PD architectures with distinct shapes that were retained even in the absence of the DNA origami template.